THE IMPLEMENTATION OF BUSINESS MODEL CANVAS (BMC) TO IMPROVE STUDENTS’ ENTREPRENEURSHIP MINDSET - Anaseputri Jamira; Nur Agustiningsih; Yulita Febriani (Dinasti Publisher, 2021)
The purpose of this study is to understand the implementation Business Model Canvas (BMC) to improve students’ entrepreneurship mindset. There is a gap from previous researches that using traditional research which just focus to develop theory. Action Research gives appropriate approach to improve work or study situation effectively and efficiency. In each cycle in the Level 2 Action Research Method using descriptive statistical analysis techniques through a comparison of the average students' entrepreneurship mindset before and after the application of the BMC method. There are 84 students who participated in this research. The results show that the hypothesis which indicates the BMC method can increase the students' entrepreneurship mindset is empirically proven. The BMC method deserves to be introduced to students. Students have knowledge about how to start a business, and have the courage, ability to create, and innovate and have a high interest in starting a business.